The Effects of an Integrating Thai Traditional Medicine Model and Nutrition Therapy to Knowledge and Fasting Blood Sugar on the Diabetes Risk Group in Non-Communicable Disease Clinic, Phunphin Hospital, Suratthani Province - Petchoom, Molticha; Eamchunprathip, Sadakan (Princess of Naradhiwas University Journal, 2023)
This quasi-experimental research as two-group, pre-posttest design aimed to compare between knowledge and blood glucose levels before and after the Thai integration program, A traditional medicine combined with nutritional therapy program. This compared between the experimental and control group. The sixty samples were diabetic risk patients’ group who received services at chronic disease clinic of Phun Phin Hospital, Surat Thani Province. The research instruments consisted of 1) the Thai integrating traditional medicine program with nutrition therapy, 2) media teaching model, and 3) nutritional counseling manuals. The validity were done by 3 experts, CVI = 0.98. The research tools consisted of 1) an assessment questionnaire for knowledge on the use of herbs to reduce sugar levels, dining and self-care 2) blood glucose level assessment, CVI value = 0.97. The confidence value of the comprehension questionnaire using KR-20 was 0.86. Data analysis was descriptive statistics, compared by t-test and paired t-test. The results revealed that the experimental group had the average knowledge scores on the use of herbs to reduce sugar levels, dining and self-care was higher than the control group, but the blood sugar level was lower than the control group. When compared within the experimental group, it was found that the knowledge of using herbs to reduce sugar levels, dining and self-care after the experiment was higher than before the experiment, but the blood sugar level was lower than before the experiment.